White Knights and the Corporate Governance of Hostile Takeovers - Riccardo Calcagno; Sonia Falconieri (Tinbergen Institute, 2008)
We analyze the dynamics of takeover contests where hostile raiders compete against white knights involved by a lead blockholder of the target firm (the incumbent). We assume that the incumbent has the power to bargain with the potential bidders to set a minimum takeover price. We characterize the conditions under which a white knight wins the takeover contest despite the smaller value of its synergies as compared to those of the hostile bidder. The paper provides a new explanation for the reason why we observe so few hostile takeovers in reality; moreover, it sheds some light on the effectiveness of white knights as an anti-takeover device and the role played by leading minority blockholders in the market for corporate control.
Keywords: D44; G34; 330; Hostile takeovers; white knights; Nash bargaining; Übernahme; Corporate Governance; Eigentümerstruktur; Auktionstheorie; Verhandlungstheorie